The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Causes and analytical impacts of missing data in RADseq phylogenetics: Insights from an African frog ( Afrixalus ) - Marco Crotti; Christopher D. Barratt; Simon P. Loader; David J. Gower; Jeffrey W. Streicher (Zoologica Scripta, 2019)
Restriction site‐associated DNA sequencing (RADseq) has emerged as a useful tool in systematics and population genomics. A common feature of RADseq data sets is that they contain missing data that arise from multiple sources including genealogical sampling bias, assembly methodology and sequencing error. Many RADseq studies have demonstrated that allowing sites (single nucleotide polymorphisms, SNPs) with missing data can increase support for phylogenetic hypotheses. Two non‐mutually exclusive explanations for this observation are that (a) larger data sets contain more phylogenetic information; and (b) excluding missing data disproportionally removes sites with the highest mutation rates, causing the exclusion of characters that are likely variable and informative. Using a RADseq data set derived from the East African banana frog, Afrixalus fornasini (up to 1.1 million SNPs), we found that missing data thresholds were positively correlated with the proportion of parsimony‐informative sites and mean branch support. Using three proxies for estimating site‐specific rate, we found that the most conservative missing data strategies excluded rapidly evolving sites, with four‐state sites present only when allowing ≥60% missing data per SNP. Topological similarity among estimated phylogenies was highest for the data sets with ≥60% missing data per SNP. Our results suggest that several desirable phylogenetic qualities were observed when allowing ≥60% missing data per SNP. However, at the highest missing data thresholds (80% and 90% missing data per SNP), we observed differences in performance between high‐ and mixed‐weight DNA extraction samples, which may indicate there are trade‐offs to consider when using degraded genomic template with RADseq protocols.

Vanishing refuge? Testing the forest refuge hypothesis in coastal East Africa using genome‐wide sequence data for seven amphibians - Christopher D. Barratt; Beryl A. Bwong; Robert Jehle; H. Christoph Liedtke; Peter Nagel; Renske E. Onstein; Daniel M. Portik; Jeffrey W. Streicher; Simon P. Loader (Molecular Ecology, 2018)
High‐throughput sequencing data have greatly improved our ability to understand the processes that contribute to current biodiversity patterns. The “vanishing refuge” diversification model is speculated for the coastal forests of eastern Africa, whereby some taxa have persisted and diversified between forest refugia, while others have switched to becoming generalists also present in non‐forest habitats. Complex arrangements of geographical barriers (hydrology and topography) and ecological gradients between forest and non‐forest habitats may have further influenced the region's biodiversity, but elucidation of general diversification processes has been limited by lack of suitable data. Here, we explicitly test alternative diversification modes in the coastal forests using genome‐wide single nucleotide polymorphisms, mtDNA, spatial and environmental data for three forest ( Arthroleptis xenodactyloides , Leptopelis flavomaculatus and Afrixalus sylvaticus ) and four generalist ( Afrixalus fornasini , A. delicatus , Leptopelis concolor and Leptopelis argenteus ) amphibians. Multiple analyses provide insight about divergence times, spatial population structure, dispersal barriers, environmental stability and demographic history. We reveal highly congruent intra‐specific diversity and population structure across taxa, with most divergences occurring during the late Pliocene and Pleistocene. Although stability models support the existence of some forest refugia, dispersal barriers and demographic models point towards idiosyncratic diversification modes across taxa. We identify a consistent role for riverine barriers in the diversification of generalist taxa, but mechanisms of diversification are more complex for forest taxa and potentially include topographical barriers, forest refugia and ecological gradients. Our work demonstrates the complexity of diversification processes in this region, which vary between forest and generalist taxa, but also for ecologically similar species with shared population boundaries.

The 8.2‐ka BP event in north‐eastern North America: first combined oxygen and hydrogen isotopic data from peat in Newfoundland - T. J. Daley; K. E. Barber; P. D. M. Hughes; N. J. Loader; M. Leuenberger; F. A. Street‐Perrott (Journal of Quaternary Science, 2016)
Finding direct evidence for atmospheric circulation change in terrestrial records of Holocene climate variability remains a fundamental challenge. Here we present the first combined stable oxygen and hydrogen isotopic palaeorecord from a peatland core in Newfoundland, Canada. Sphagnum cellulose samples were isolated from a core from Nordan's Pond Bog, Newfoundland, and analysed for δD values. Combined with existing δ 18 O data, the resulting δD/δ 18 O bi‐plot correlates directly with existing measurements of the modern (late 20th century) isotopic composition of precipitation from GNIP stations in Nova Scotia and Labrador, implying a close relationship between the estimated isotopic composition of source water used by the mosses and that of the source precipitation. We use the relative variations between the two isotope records to test the hypothesis that atmospheric circulation changed in the millennium following the 8.2‐ka BP climate event. The data reveal a secondary complex isotopic response ∼200 years (8250–8050 a BP) after a primary oxygen isotopic event that is widespread in the north Atlantic region. This secondary event is characterized by a divergence in oxygen and hydrogen isotope records that can most plausibly be explained by the augmentation of precipitation moisture from a more distant and more continental vapour source.

Measurements of hydrogen, oxygen and carbon isotope variability in Sphagnum moss along a micro‐topographical gradient in a southern Patagonian peatland - N. J. Loader; F. A. Street‐Perrott; D. Mauquoy; T. P. Roland; S. van Bellen; T. J. Daley; D. Davies; P. D. M. Hughes; V. O. Pancotto; G. H. F. Young; M. J. Amesbury; D. J. Charman; et al. (Journal of Quaternary Science, 2016)
Peat archives offer a diverse range of physical and chemical proxies from which it is possible to study past environmental and ecological changes. Direct numerical calibration and verification is difficult so process‐based and mechanistic studies are therefore required to establish and quantify links between environmental changes and their associated proxy‐responses. Traditional ‘space‐for‐time’ calibrations provide a solution to this calibration problem, but are often unable to isolate a single environmental variable from other potentially confounding variables. In this study, we explored the potential of a site‐specific ‘space‐for‐time’ approach applied to a hummock‐hollow transect on an ombrotrophic raised bog in Patagonia, southern Chile. Coupled stable carbon, oxygen and hydrogen isotopic measurements were made on individual samples of Sphagnum moss cellulose and compared with plant‐associated waters, local hydrology, temperature and relative humidity, sampled at the same points along the study transect. Results reveal a range of environmental responses, which were supported by plant‐physiological models in the case of carbon and oxygen isotopes. For hydrogen isotopes, the results obtained from cellulose indicated a need for further research into hydrogen isotope fractionation in Sphagnum . We recommend conducting site‐specific characterization of plant response to support the development of peat‐based isotope records for palaeoenvironmental research, and where logistically possible, that monitoring is conducted over timescales appropriate to the time‐integrative nature of the Sphagnum record.

Testate amoebae as a proxy for reconstructing Holocene water table dynamics in southern Patagonian peat bogs - SIMON VAN BELLEN; DMITRI MAUQUOY; RICHARD J. PAYNE; THOMAS P. ROLAND; TIM J. DALEY; PAUL D. M. HUGHES; NEIL J. LOADER; F. ALAYNE STREET‐PERROTT; EMMA M. RICE; VERÓNICA A. PANCOTTO (Journal of Quaternary Science, 2014)
Testate amoebae are abundant and diverse in Sphagnum peat bogs and have been used extensively as indicators of past water table depths. Although these unicellular protists are widely dispersed with globally similar hydrological preferences, regional variations in communities demand region‐specific transfer functions. Here we present the first transfer function for southern Patagonian bogs, based on 154 surface samples obtained from transects in five bogs sampled in 2012 and 2013. Significant variance was explained by pH, electrical conductivity and, in particular, water table depth. Transfer functions for water table were constructed using weighted averaging and evaluated by cross‐validation and independent test sets. The optimal transfer function has predictive ability, but relatively high prediction errors given the wide range in sampled water tables. The use of independent test sets, as well as cross‐validation, allows a more rigorous assessment of model performance than most previous studies. For a subset of locations we compare surface and subsurface samples to demonstrate significant differences in community composition, possibly due to vertical zonation. Our results provide the first quantification of hydrological optima and tolerances for several rare species, which may include Southern Hemisphere endemics and pave the way for palaeohydrological reconstructions in southern Patagonian bogs.

The application of tree-rings and stable isotopes for reconstructions of climate conditions in the Russian Altai - O. V. Sidorova; R. T. W. Siegwolf; V. S. Myglan; D. V. Ovchinnikov; V. V. Shishov; G. Helle; N. J. Loader; M. Saurer (Climatic Change, 2013)

Central England temperature since AD 1850: the potential of stable carbon isotopes in British oak trees to reconstruct past summer temperatures - G. H. F. Young; R. J. Bale; N. J. Loader; D. Mccarroll; N. Nayling; N. Vousden (Journal of Quaternary Science, 2012)
In regions with seasonal temperate climatic regimes, tree growth is rarely controlled by any single environmental factor. As a consequence, the development of robust palaeoclimate reconstructions has proved challenging. Tree‐ring stable carbon isotope ratios (δ 13 C), however, are controlled primarily by photosynthetic rate, not by net growth. Therefore, at sites where climatic controls on tree‐ring growth are not strongly expressed, a robust (isotopic) palaeoclimate signal may still potentially be preserved. This hypothesis was tested using a 160‐year record of δ 13 C measured from the pooled latewood cellulose of six Quercus petraea L. (sessile oak) trees from Allt Lan‐las in West Wales, UK. Raw δ 13 C values were corrected for changes in the isotopic ratio of atmospheric carbon dioxide and for changes in the behaviour of trees due to the increasing availability of atmospheric CO 2 since AD 1850. Strong correlations with local summer temperature and sunshine are reported, and also with the Central England Temperature record over the full length of the isotopic chronology (AD 1850–2010) ( r = 0.69, P

Characterisation of nine microsatellite loci in the caecilian amphibian Boulengerula uluguruensis (Gymnophiona), and their cross-species utility in three congeneric species - Christopher D. Barratt; Gavin J. Horsburgh; Deborah A. Dawson; David J. Gower; Mark Wilkinson; Simon P. Loader; Robert Jehle (Conservation Genetics Resources, 2012)

Refuge use by fish as a function of body weight changes - J. Krause; S. P. Loader; E. Kirkman; G. D. Ruxton (acta ethologica, 1999)